Nutrient stoichiometric and resorption characteristics of the petals of four common urban greening Rosaceae tree species - Song, Dan; Liu, Shuting; Fan, Lide; Yang, Jinyan; Li, Haifang; Xia, Yujie; Li, Yuwu (Frontiers in Plant Science, 2023)
Nutrient resorption efficiency and stoichiometric ratios are important strategies for understanding plants. The present study examined whether or not the nutrient resorption process of plant petals is similar to that of leaves and other vegetative organs, as well as the nutrient restriction status of the whole flowering process of plants in urban ecosystems. Four Rosaceae tree species, Prunus yedoensis Matsum, Prunus serrulata var. lannesiana, Malus micromalus Makino, and Prunus cerasifera ‘Atropurpurea’, were selected as urban greening species to analyze the contents of C, N, P, and K elements in the petals and their stoichiometric ratios and nutrient resorption efficiencies. The results show interspecific differences in nutrient contents, stoichiometric ratios, and nutrient resorption efficiency of the fresh petals and petal litter of the four Rosaceae species. The nutrient resorption process was similar to that of the leaves before the petals fell. The nutrient contents of petals were higher than that of leaves at the global level, but the stoichiometric ratio and nutrient resorption efficiency of petals were lower. According to the "relative resorption hypothesis", N was limiting during the entire flowering period. The nutrient resorption efficiency of petals was positively correlated with nutrient variation. The correlation between the nutrient resorption efficiency of petals with nutrient content and stoichiometric ratio of petal litter was stronger.